AKTIVITAS TUMBUHAN KELOR (Moringa oleifera) DALAM PENYEMBUHAN TUKAK PEPTIK: LITERATURE REVIEW - Kadek Dian Widyapurwanti (Jurnal Medika Hutama, 2022)
Background: Peptic ulcer is one of the gastrointestinal disorders that can have serious effects when not handled properly. In 2020, the mortality rate of peptic ulcers was reported to reach 14.95%. Many people have done peptic ulcer therapy by using synthetic drugs. To improve healing and reduce side effects caused by synthetic drugs, it is necessary to support therapy using plants that have healing activity in peptic ulcers. Moringa oleifera is one of the plants reported to have anti-ulcer activity. Objective: This work aims to examine the effectiveness of the plant M.oleifera in the treatment of peptic ulcers. Methods: Data analysis was carried out by reviewing the scientific literature. Results: Moringa plant parts consisting of leaves, root bark, seeds, and bark were reported to have anti-ulcer activity, anti-ulcer activity was caused by phytochemical content in Moringa plants such as flavonoids, isothiocyanates, tannins, alkaloids, and terpenoids. Conclusion: Moringa oleifera can be used as a therapeutic agent for peptic ulcer healing.